Characterization socioeconomic and biophysical of dairy production farms in the municipality of Pasto - Molina, Juan Pablo; Ojeda, David; Navia, Jorge Fernando; Muñoz, Diego Andrés (Revista de Ciencias Agrícolas, 2009)
Dairy production farms and the tree component within them were biophysical and socioeconomic characterized in municipality of Pasto department Nariño. Fourteen villages were chosen with a same or bigger dairy production to a thousand daily liters, where carries out a stratified aleatory sampling applying interview to 200 farms selected at random, carrying out an analysis of main components and an analysis of multiple correspondences; identifying a silvopastoral system bovine-milk within for small, medium and big producers. The production systems differ among if, for the number of livestock heads and for dairy production in their farms. Same arboreal species standing out Bacharis sp, Weinmania pubescens, Miconia theacens, Acacia decurrens, Alnus acuminata and Eucalyptus globulus, besides finding managed natural and improved pastures in a mixed way, represented by Holcus lanatus, Pennisetum clandestinum, Lolium multiflorum. These properties have had cattle holstein and criollo for the dairy production. In most of farms be reported the system productive potato-grass-bovine-milk, managed in a traditional way, prevailing potato varieties (Solanum tuberosum) as Diacol capiro, Pastusa Suprema, Amarilla y Roja. The relationship between tree component and the escalation with the production systems in the farms doesn't identify, because the producers ignore the potential paper of the trees in their production system.